Design and performance analysis of PV grid-tied system with energy storage system - Jerry Kumar; Nanik Ram Parhyar; Manoj Kumar Panjwani; Danish Khan (International Journal of Electrical and Computer Engineering (IJECE), 2021)
With the increasing demand for solar energy as a renewable source has brought up new challenges in the field of energy. However, one of the main advantages of photovoltaic (PV) power generation technology is that it can be directly connected to the grid power generation system and meet the demand of increasing energy consumption. Large-scale PV grid-connected power generation system put forward new challenges on the stability and control of the power grid and the grid-tied photovoltaic system with an energy storage system. To overcome these problems, the PV grid-tied system consisted of 8 kW PV array with energy storage system is designed, and in this system, the battery components can be coupled with the power grid by AC or DC mode. In addition, the feasibility and flexibility of the maximum power point tracking (MPPT) charge controller are verified through the dynamic model built in the residential solar PV system. Through the feasibility verification of the model control mode and the strategy control, the grid-connected PV system combined with reserve battery storage can effectively improve the stability of the system and reduce the cost of power generation. To analyze the performance of the grid-tied system, some real-time simulations are performed with the help of the system advisor model (SAM) that ensures the satisfactory working of the designed PV grid-tied System.